Radovan III . Radovan III - Draškić, Ljubomir (RTV Beograd, 1983)
This bizarre TV-drama tells the story of a lost identity caused by socialist “progress.” In search of a better life, Radovan moved from his native village to the city suburbs where he lives with his weird family on the 12th floor. His first daughter was raised as a son and is now a truck driver deprived of any femininity. His other daughter has been pregnant for five years already since young Vilotić, the father, fled to America and Radovan does not allow her to give birth until she marries. Persuaded by official propaganda that the “enemy” is omnipresent, he starts his vendetta against the Vilotić family and imprisons one of them and forces him to marry pregmant Georgina. Radovan’s wife rejects the settlement, seeing in the prisoner an ideal surrogate for her sexually inoperative husband. Though Radovan appears powerful, he is in a fact utterly confused. In the name of “great ideals,” he has forgotten his roots and destroyed any prospects for a prosperous future for his family. When his nearest take the side of the “enemy”, Radovan, in self-betrayal, ultimately does the same.